Radiation dose obtained from abdominal computed radiography: comparison between supine and prone positions - Abdul Aziz Ismail,; Mazlyfarina Mohamad,; Rozilawati Ahmad,; Ahmad Bazlie Abdul Kadir, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aims of this study were to compare the entrance surface dose (ESD) between anteroposterior (AP) supine with posteroanterior (PA) prone projection of computed radiography (CR) abdominal examination and to determine the relationship between body mass index (BMI) and ESD of a patient. AP supine and PA prone projections on the same patients for CR abdominal examination of intravenous urography (IVU) were acquired on 50 patients at Hospital Raja Permaisuri Bainun, Ipoh. All the radiographic examinations were carried out on a Siemens Multixtop general x-ray unit and the images were processed with CR Carestream Direct view Max. Entrance surface dose (ESD) in miligray (mGy) was measured using optical stimulated luminescence dosimeters (OSLD) calibrated by the Malaysian Nuclear Agency. Data were analyzed using dependent t-test comparing the AP and PA projections on the same subject and Pearson correlation was used to determine the relationship between BMI and percentage of reduction of ESD. Results showed a significant different (p < 0.01) between AP supine (mean ESD = 6.42 ± 7.13 mGy) and PA prone (mean ESD = 3.92 ± 3.56 mGy) projection at all BMI. The BMI has a positive correlation with percentage of reduction of ESD (r = 0. 61) and was statistically significant (p < 0.01). In conclusion, PA abdomen prone projection significantly reduces the radiation dose and there is a positive correlation between BMI and percentage of reduction of ESD. The use of PA prone projection for CR abdominal examination should be considered as the routine projection at all BMIs level. Awareness that as the BMI increases the ESD also increases at a moderate positive linear relationship.